The Challenges in Teaching Writing through Cooperative Integrated Reading and Composition (CIRC) Strategy - Sakkir, Geminastiti; Haturrahma, Mufti (ARRUS Journal of Social Sciences and Humanities, 2023)
This research aimed to know the challenges in teaching Cooperative Integrated Reading and Composition (CIRC) in teaching writing. The researcher applied a qualitative research design. The instruments of the research were an observation sheet and an interview guide. The participants of the research were two teachers in second grade at SMP Telkom Makassar. The result showed that the implementation of CIRC in teaching writing is good and by the actual procedure, during the process implementation of CIRC had challenges when that strategy was applied to teaching writing skills in the classroom. The teacher must prepare teaching materials that will be discussed in class, the material must be by the needs for implementing this strategy, and the teacher must make time efficient in the class, because the implementation process with the CIRC strategy is applied systematically and the teacher must manage the class in a conducive manner, because of the collaborative implementation of the CIRC strategy. The teachers also modify this strategy in implementing CIRC the teachers apply placement tests before making a group based on characteristics and also group selection that is formed in high, medium, and low-ability students. These indicators include benefits such as strengthening students' public, assisting them in being more critical thinkers, and also increased motivation and writing skills. CIRC can contribute to developing students' abilities to be more creative, independent, collaborative, communicative, and self-confident CIRC can also improve vocabulary mastery, familiarize students with conveying ideas by extending the topic, and build students' self-confidence in the area of writing skill. As a result, they can communicate and improve their writing skill. The other indicator is the difficulties that students face in implementing CIRC, such as taking a long time to apply it in class optimally.